Translation Techniques in Translating Cultural Issues in the Indonesian Religious Tourism Brochure in Semarang City - Jafar Sodiq; Theresia Cicik Sophia Budiman; Nur Hidayat (Universitas PGRI Semarang, 2020)
ABSTRACT Many foreigners visit Indonesia especially Semarang City for doing some business, research, Javanese Cultural studies or just for vacation. As foreign tourists, they only depend on tourism brochures or use Google Map to find the places they want to visit. Often, the English-translated tourism brochures contain untranslatable words or phrases. This research is aimed at finding out the translation techniques used to translate the cultural issues in the Indonesian tourism brochure texts especially the religious tourist destinations in Semarang City. This research is descriptive qualitative type and uses the tourism brochure texts as the sample. The results of this research show that several translation techniques are used in to translate the Indonesian texts into English which include (1) pure borrowing; (2) established equivalence; (3) pure borrowing-established equivalence; (4) deletion; (5) pure borrowing-deletion; (6) generalization; (7) modulation; (8) generalization-pure borrowing; (9) pure borrowing-modulation; (10) modulation-deletion. The dominant techniques are pure borrowing and established equivalence which are associated with the high accuracy in translating the cultural issues in the Indonesian tourism brochure texts especially the religious tourist destinations in Semarang City. Keywords:translation techniques, cultural issues, tourism brochure especially the religious tourist destination, Semarang City